PENGUATAN PELAJAR PANCASILA DENGAN MEWUJUDKAN SEKOLAH RAMAH ANAK MELALUI SOSIALISASI ANTI-BULLYING DI MI BIRRUL WALIDAIN NW 2 RENSING KABUPATEN LOMBOK TIMUR - Zulkarnain, Zulkarnain; Asfhin, M.; Anggriani, Rini; Mahharani, Ayu; Aggriani, Nuning; Sumiyati, Sumiyati; Huda, Nurul (Jurnal Abdi Insani, 2024)
The phenomenon of bullying has long been part of the dynamics in schools. Evidence from the ground reveals that schools in Indonesia continue to grapple with bullying cases, implying that the goal of cultivating Pancasila students with noble character remains unfulfilled. This community service activity aims to instill noble character in Pancasila students and foster a child-friendly, bullying-free school environment through anti-bullying socialization, thereby measuring the level of student knowledge about bullying in schools. This community service activity involves socialization through lectures and question-and-answer sessions. The target partners in this activity are students of MI Birrul Walidain NW 2 Rensing, consisting of 50 students spread from grades IV-VI and accompanied by 5 teachers as companions. Evaluation techniques in this activity include questionnaires, interviews, and observations. The evaluation yielded a pretest score of 42% (21 students), which subsequently increased to 72% (36 students) based on the posttest score. These results indicate that there was an increase in participant knowledge before and after the socialization was carried out.